Supramolecular Cocrystals : Synthesis, Structural Characterizations And Theoretical Studies - Che Khalib, Nuridayanti (2017)
In this research work, nineteen novel cocrystals of various carboxylic acids and bases have been investigated using spectroscopic methods such as powder and single crystal X-ray Crystallography, Infrared (FT-IR) and Nuclear Magnetic Resonance (NMR). The theoretical calculations of the cocrystals were performed using Density Functional Theory (DFT) method and Hirshfeld Surfaces analysis. Generally, the DFT and experimental results are comparable to each other except for the conformational difference around the carboxyl groups. Spectroscopic properties of the cocrystals were examined by FT-IR and NMR. Apart from the pKa values prediction, single crystal and powder X-ray diffractions show that all the samples are cocrystals.